Living Values Implementation and Technology of Islam Knowledge In Globalization The Perspective of Ibnu Sina - Mohammad Faizin; Maulana Hakim Al Rasyid; Arya Bagus Anindita; Achmad Syarif Hidayatullah (El-Idare, 2022)
Education is an activity carried out by humans from birth to death which has the goal of increasing intelligence, both knowledge, skills or other knowledge so as to support human development in life. Islamic Education is a science that guides people both physically and spiritually based on Islamic knowledge both from the hadith, the Koran and other sources so that humans walk on the right path. The technology here is explained in Islamic Education learning assistance both in helping to collect assigments, find sources, or in the process of tracing materials so that the learning process goes well in the era of globalization.